2011
DOI: 10.1200/jop.2011.000351
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Palliative Medicine Into Routine Oncological Care: What Does the Evidence Show Us?

Abstract: There is phase III evidence that formal assessment of patients' symptoms and quality of life can lead to measurable improvements in quality of life. Quality of life assessments using validated tools should become routine in cancer centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…1–3 Data strongly support that patients with non-small cell lung cancer (NSCLC) experience high symptom burdens, many comorbidities, and psychosocial-spiritual concerns related to the diagnosis. 410 The key study by Temel and colleagues 11 , reporting on NSCLC patients receiving concurrent palliative care, gained much attention when their outcomes revealed not only improved symptoms but prolonged survival.…”
mentioning
confidence: 99%
“…1–3 Data strongly support that patients with non-small cell lung cancer (NSCLC) experience high symptom burdens, many comorbidities, and psychosocial-spiritual concerns related to the diagnosis. 410 The key study by Temel and colleagues 11 , reporting on NSCLC patients receiving concurrent palliative care, gained much attention when their outcomes revealed not only improved symptoms but prolonged survival.…”
mentioning
confidence: 99%
“…Even with supporting evidence of the benefits of PC in cancer care, it is not being implemented into routine oncologic care (Ferris et al, 2009;IOM, 2001IOM, , 2013Temel et al, 2010;Debono, 2011;Smith et al, 2012;Storey et al, 2011).…”
Section: Identifying the Need For Pc In Standard Oncologic Carementioning
confidence: 99%
“…3 The subspecialty of Hospice and Palliative Medicine has been formally recognized by the American Board of Internal Medicine. 4 The American Society of Clinical Oncology (ASCO) also published an update on the current state of the science in palliative cancer care. 5 In this article, palliative cancer care has been defined as the “integration into cancer care of therapies that address multiple issues that cause suffering for patients and their families and impact their life quality.” 5 The article further states that the effective provision of palliative cancer care “requires an interdisciplinary team that can provide care in all patient settings, including outpatient clinics.” 5 According to the report, comprehensive cancer care must include palliative care as an integral part of patient and family care.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the ever-expanding evidence that supports the efficacy of palliative care in improving key patient-reported outcomes such as quality of life (QOL), depression, and overall survival 4, 7 , challenges and barriers remain in the integration of models of palliative care into routine oncologic care in ambulatory settings. 4, 6, 810 A survey conducted by Hui and colleagues found that in all NCI-designated cancer centers, only 60% had a formal outpatient palliative medicine clinic, and this number is even smaller for non-NCI designated cancer centers (22%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation